I want to die but I want to eat tteokbokki - Paek, Se-hŭi, 1990- (Bloomsbury Publishing, 2022)
"Baek Sehee is a successful young social media director at a publishing house when she begins seeing a psychiatrist about her - what to call it? - depression? She feels persistently low, anxious, endlessly self-doubting, but also highly judgmental of others. She hides her feelings well at work and with friends; adept at performing the calmness, even ease, her lifestyle demands. The effort is exhausting, overwhelming, and keeps her from forming deep relationships. This can't be normal. But if she's so hopeless, why can she always summon a desire for her favourite street food, the hot, spicy rice cake, tteokbokki? Is this just what life is like? Recording her dialogues with her psychiatrist over a 12-week period, Baek begins to disentangle the feedback loops, knee-jerk reactions and harmful behaviours that keep her locked in a cycle of self-abuse"--provided by publisher.